Establishing an Inclusive Legal Framework for People with Disabilities in Islamic Higher Education Institutions in Indonesia - Setiawan Nur Heriyanto, Dodik; Syarahbil Hudzaifi, Muhammad (KnE Social Sciences, 2023)
People with disabilities often have unequal access to education. Most higher education institutions and universities in Indonesia still have discriminatory practices. The main factors that affect people with disabilities are the lack of infrastructure and limited budget allocation. In Indonesian Islamic higher education institutions, many policies related to the development of education have not considered persons with disabilities. This study used a normative research method which examined legal policies for people with disabilities in Islamic universities in Indonesia. This study is essential to understand the legal policies in Islamic universities for people with disabilities. In addition, this study also provided an analysis of the compatibility between Fiqh related to equality for people with disabilities and legal policies in Islamic universities in Indonesia. This study concluded that most Islamic universities in Indonesia do not have legal policies that support people with disabilities and ensure their equal treatment at the university. For this reason, this study recommended that the ministry, which has the duty and authority in the field of education, establish guidelines and ensure that all universities in Indonesia provide accessibility to persons with disabilities. Keywords: Equality, Person with Disabilities, Islamic Higher Education